Expression of human epidermal growth factor in pichia pastoris and optimization of fermentation conditions - Eissazadeh, Samira (2012)
Human epidermal growth factor (hEGF) is a 6.2 kD polypeptide secreted by human tissues into the body fluid. It carries multiple biological functions including induction of tissue proliferation and differentiation, a process that is important in tissue repair. Because of this function, hEGF is widely used in various medical and industrial applications such as for wound healing, corneal transplant and treatment of gastric ulcers. As a result, the demand for hEGF supply for local consumption is always high, and there is a need for enough and cheap local supply of this protein. However, local production of hEGF especially in large commercial scales has not been successful due to various technical challenges. This study was carried out to express the hEGF gene in the yeast, Pichia pastoris GS115 using a commercially available expression vector equipped with a specific signal peptide that directs the transportation of the hEGF protein into the culture medium. The performance of the expression system for hEGF production was enhanced by optimizing the fermentation conditions of the yeast. The hEGF gene was ligated into the pPIC9K expression vector, and then integrated into the yeast’s genome by electroporation. The hEGF was assayed by using an ELISA-based system and the recombinant cell line that produced the highest hEGF was then used in the optimization of the fermentation conditions. In addition, the amount of methanol, an inducer for the expression system was also optimised. The highest amount of hEGF secreted into the medium was obtained from clone B1 of the recombinant yeast with an average yield of 2.27 μg/ml. This was obtained through an induction of the yeast culture with 0.5% (v/v) methanol for 60 hours. The best medium for the optimal hEGF production was BMMY buffered at a pH range of 6.0 and 7.0. Within this pH range, the difference in hEGF production was not significant. Two fermentation conditions commonly known to affect heterologous protein production (pH and temperature) were analyzed by using the artificial neural network (ANN). Changes in both pH and temperature significantly affected the hEGF production with the pH change had slightly higher impact on hEGF production than variations in the temperature. As anticipated from the model, the production of hEGF was decreased when the pH of the culture medium was lower than 6.0, or when the temperature was lower than 30°C. As a conclusion, hEGF was correctly secreted into the culture media of the recombinant P. pastoris as anticipated from the properties of the expression vector used. The amount of hEGF secreted into the medium was affected by the fermentation conditions especially the types of culture media used, the pH of the culture media and incubation temperature.